Hacking Gender and Technology in Journalism - De Vuyst, Sara (Taylor & Francis, 2021)
Hacking Gender and Technology in Journalism addresses the question of whether journalism’s new digital spaces suffer from the same gendered structures as traditional media organisations, or whether they go beyond such bias.